Viva Chicano - Bonham, Frank (New York, E. P. Dutton, 1970)
Keeny, a Mexican-American on parole, feels he must not return to the atmosphere of his home and neighborhood and devises a solution to the problem.
HBK.
Keywords: Mexican Americans -- Fiction; Juvenile delinquency -- Fiction